The Determinants Of World Islamic Banks Efficiency: Empirical Analysis Using A Non Parametric Approach - Nafti, Olfa; Boumediene, Salem Lotfi; Khouaja, Slim; Ayed, Wassim Ben (Journal of Applied Business Research, 2017)
The purpose of this paper is to analyze the efficiency of Islamic banks operating in different countries, over the period 2006-2009. We applied a non-parametric approach, or a Data Envelopment Analysis (DEA), that utilizes both the constant returns to scale (CRS) and the variable returns to scale (VRS) assumptions to offer measures of the technical and scale efficiency. The outcomes reveal a considerable degree of dispersion of technical efficiency between banks within the sample of the year-to-year basis. To inspect the determinants of efficiency, we apply the panel regression analysis. In fact, we used panel regression analysis in order to explain the variation in the dependent variable (calculated efficiencies) by a set of independent variables, such as banks size, asset quality, management capability, liquidity, sensitivity to markets risks, and capitalization. We find that banks with higher liquidity and a good management capability are more likely to operate at higher levels of technical efficiency. In addition, the results show that size, seem to contribute negatively to the evolution of efficiency scores of Islamic banks operating in the world.